PROPOLIS EXTRACT AS ANTI-CORROSIVE AGENT INHIBITS METAL IONIC RELEASE FROM ORTHODONTIC BRACKETS - Grahita Aditya; Erdianto Setya Wardhana; Islamy Rahma Hutami; Sandy Christiono; Rosa Pratiwi (Dentino: Jurnal Kedokteran Gigi, 2024)
Background: A combination of nickel (Ni), chromium (Cr), and iron (Fe) can be found in the stainless steel orthodontic bracket. Ion release takes place as a result of the chemical interaction between metals and the oral environment, which leads to the potential of hypersensitivity during fixed orthodontic treatment. Propolis contains phytochemicals that have the ability to reduce corrosion, making it a potential treatment option. Purpose: to determine the release of Ni, Cr, and Fe in metal brackets in an 8.2% propolis solutionMethod: Four sets of six brackets were made from 24 brackets. Artificial saliva, sodium fluoride, sterilized distilled water (aquabidest), and 8.2% propolis were applied to these brackets. After incubating at 37°C for seven days, ICP EOS measured the metal ions Ni, Cr, and Fe. The analysis revealed significant differences (p<0.05) in ionic release of Ni, Cr, and Fe among groups exposed to sterilized distilled water (aquabidest) and an 8.2% propolis solution. Additionally, the Mann-Whitney test showed substantial Ni ion release differences (p<0.05) between 8.2% propolis solution and sterilized distilled water. The 8.2% propolis solution and sodium fluoride solution released Cr ions differently. Fe ion levels differed between propolis solution 8.2%, sodium fluoride solution, sterilized distilled water, and fake saliva. Conclusion:  Propolis affects metal bracket ionic release of Ni, Cr, and Fe. Keywords : Cr and Fe, ions of Ni, propolis solution, Stainless steel bracket